Controlling valley-polarisation in graphene via tailored light pulses. (29th December 2021) - Mrudul, M S; Dixit, Gopal
Abstract: Analogous to charge and spin, electrons in solids endows an additional degree of freedom: the valley pseudospin. Two-dimensional hexagonal materials such as graphene exhibit two valleys, labelled as K and K ′. These two valleys have the potential to realise logical operations in two-dimensional materials. Obtaining the desired control over valley polarisation between the two valleys is a prerequisite for the logical operations. Recently, it was shown that two counter-rotating circularly polarised laser pulses can induce a significant valley-polarisation in graphene. The main focus of the present work is to optimise the valley polarisation in monolayer graphene by controlling different laser parameters, such as wavelength, intensity ratio, frequency ratio and sub-cycle phase in two counter-rotating circularly polarised laser setup. Moreover, an alternate approach, based on single or few-cycle linearly polarised laser pulse, is also explored to induce significant valley polarisation in graphene. Our work could help experimentalists to choose a suitable method with optimised parameter space to obtain the desired control over valley polarisation in monolayer graphene.